Religious (Islamic) Character Education Based on Local Wisdom: Systematic Study 2014-2024 - Arif, Muhamad; Chapakiya, Suraiya (AT-THULLAB : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
The urgency of implementing religious character education must be carried out since elementary school students, starting from choosing the best strategy in implementing religious character education, the role of subject teachers, and integration with the local wisdom of society is the best space in implementing religious character education. So in this study, researchers use the systematic literature review method by optimizing three global databases, namely Google Scholar, Scopus, and WOS, through the publish or perlis application, with themes (keywords) in the 2014-2024 range, combined with the data analysis process researchers use five stages, starting from data collection planning, data identification, selection of feasible data and conducting meta-analysis with a comparison of social theory. Implementing religious character education in elementary schools can be done in various ways, starting from programs implemented by optimizing integration between the government, schools, parents, and the community. In addition, religious character education can be implemented according to the challenges in each school by using local wisdom models, such as Islamic boarding schools, Maja Labo Dahu in West Nusa Tenggara, Rejang in Bengkulu, Basandi Syarak customs, Syarak Basandi Kitabullah in Padang, Sipakatau, Sipakalebbi, and Sipakainge in Makassar and Dhukutan Tawangmanggu customs. Based on these results, this study has theoretical implications for Sturt Hall’s thinking with three concepts of identity in implementing religious character education.